Designing a system for collecting policy-relevant data for the Kurdistan Region--Iraq - Berry, Sandra H., 1949-; Burger, Nicholas E.; Dogo, Harun; Kumar, Krishna B.; Malchiodi, Alessandro; Martini, Jeffrey; Mengistu, Tewodaj; Shatz, Howard J.; Smith, Alexandria C.; Usanov, Artur; Yoong, Joanne K. (RAND, 2014)
Comprehensive and reliable statistics are crucial for policy formulation in any region or country. The Kurdistan Region--Iraq (KRI) is hampered by the lack of such statistics as it aims to improve infrastructure, encourage private-sector development, attract foreign investment, and create a sustainable economy. The authors of this study, which was funded by the Kurdistan Regional Government (KRG), interviewed officials in several KRI ministries, assessed available data within the KRI, conducted cross-country benchmarking, and studied best practices in data-collection methodologies. In this volume, the authors describe the KRG's statistical institutions; identify ten high-priority areas for the KRI and the types of data that should be collected to support policymaking in these areas; and outline a system to collect and disseminate these data on an ongoing basis. The authors conclude with a series of recommendations on the topics that should be addressed by statistics legislation, the structure and oversight of data institutions, the implementation and use of surveys and censuses, and the use of administrative data. Together, these recommendations provide a road map that will help the KRG assemble the core elements of a quality data system, which, in turn, will increase the availability of data to help KRG leaders achieve their most important policy goals.